Religious identity, trust, reciprocity, and prosociality: Theory and evidence - Dhami, Sanjit; Wei, Mengxing; Mamidi, Pavan (Journal of development economics, 2024)
We use the trust and the dictator games to explore the effects of religious identity on trust, trustworthiness, prosociality, and conditional reciprocity within a beliefs-based model. We provide a novel, rigorous, theoretical model to derive the relevant predictions, which are then tested in lab-in-the-field experiments in the Indian states of Bihar and Uttar Pradesh. We find strong evidence of the effects of religious identity on the belief hierarchies, and the chosen actions, of Hindu and Muslim subjects. Priming for a religious identity has little effect on Hindu subjects but it enhances religious polarization in beliefs and actions among Muslim subjects. There is taste-based discrimination but no statistical discrimination. All our underlying assumptions on beliefs, and their dependence on priming and identity are confirmed by the data, identifying a precise beliefs-based mechanism for the effects of religious identity. More religious subjects expect greater prosociality/reciprocity and often are more prosocial/reciprocal. •Trust, trustworthiness, prosociality, reciprocity, are driven by underlying beliefs.•Priming for religion has asymmetric effects on members of different religions.•There are strong ingroup–outgroup effects of religious identity on chosen actions.•There are shared cultural values in average levels of trust and trustworthiness.•There is taste-based discrimination but no statistical discrimination.